1978
DOI: 10.1144/gsjgs.135.1.0093
|View full text |Cite
|
Sign up to set email alerts
|

Diagenetic sequences in low-permeability argillaceous sandstones

Abstract: A regular sequence of mineral paragenesis is observed in low-permeability (‘tight’), very fine-grained sandstones of brackish marine to fresh water origin in portions of the Cretaceous of the Rocky Mountains, North America. From pore throat to pore centre in these rocks, the common authigenic sequence is illite (pore throat), kaolinite, silica (pore centre), and siderite (pore centre but after silica). Associated fine- to medium-grained sandstones exhibit a sequence of quartz followed by kaolinite plus traces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Thomas 1978;Burley 1984;Kantorowicz 1984) given the right geochemical conditions (cf. Hurst and Irwin 1982) but may be of significance in terms of producing large volumes o f illite (cf.…”
Section: Mite Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Thomas 1978;Burley 1984;Kantorowicz 1984) given the right geochemical conditions (cf. Hurst and Irwin 1982) but may be of significance in terms of producing large volumes o f illite (cf.…”
Section: Mite Morphologymentioning
confidence: 99%
“…(1976), and Boles and Franks (1979, or assume illite t o be a direct precipitate (e.g. Thomas 1978;Waugh 197%;Colter and Ebbern 1979;Odom et al 1979;Guven et al 1980;H u n t and Irwin 1982). Several authors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Authigenic clays are formed by diagenetic alteration of in situ minerals in impure (e.g., arkosic sandstones, lithic arenites) and have been identified in 90% of sandstones (from a study of 785 sandstones, Wilson & Pittman, 1977). Authigenic clays precipitate within pore spaces and, although relatively minor in volume (<10%), they have been shown to significantly decrease pore connectivity and permeability by over five fold (Bjørlykke and Jahren, 1992;De Waal et al, 1988;Howard, 1992;Hurst & Nadeau, 1995;Pallatt et al, 1984;Stalder, 1973;Thomas, 1978;Wilson et al, 2013;Wilson & Pittman, 1977;Worden & Morad, 1999). Mechanisms for permeability reduction due to pore filling clays are: Precipitation of authigenic clays within the pore space which dominantly constrict pore throats (Wilson & Pittman, 1977); complex pore filling morphologies which reduce the effective porosity (porosity that contributes to permeability) by creating microporosity (Nadeau & Hurst, 1991); and porosity reduction due to the formation of water shell on the clay surfaces creating a double electric layer (DEL) and diffuse layer (Derjaguin et al, 1987).…”
Section: Influence Of Authigenic Clay Volume and Distribution On Permeabilitymentioning
confidence: 99%
“…The Upper Cretaceous Almond and Ericson formation sandstones (Mesaverde Group) of southwestern Wyoming provide good examples of the influence of clay minerals on porosity and permeability. SEM study of samples from both reservoirs 13 showed that the clay minerals differed in the two reservoir rocks, both in composition and position, within the pore system. The Almond formation reservoir rock typically contained discrete coarse kaolinite euhedra packed in some pores (Fig.…”
Section: Influence Of Clay Minerals On Productivity In Sandstone Resementioning
confidence: 99%